2018
DOI: 10.5811/westjem.2017.11.36427
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Ultrasound-guided Peritonsillar Abscess Model for Simulation Training

Abstract: IntroductionPeritonsillar abscess (PTA) is the most common deep space infection of the head and neck presenting to emergency departments.1 No commercial PTA task trainer exists for simulation training. Thus, resident physicians often perform their first PTA needle aspiration in the clinical setting, knowing that carotid artery puncture and hemorrhage are serious and devastating complications. While several low-fidelity PTA task trainers have been previously described, none allow for ultrasound image acquisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…This highlights the underutilization of ultrasound for diagnosis and treatment. Training utilizing ultrasound for PTA drainage has been found to increase a resident's comfort level with PTA management [ 11 ]. The ED at the institution is the primary location for a large Emergency Medicine residency program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the underutilization of ultrasound for diagnosis and treatment. Training utilizing ultrasound for PTA drainage has been found to increase a resident's comfort level with PTA management [ 11 ]. The ED at the institution is the primary location for a large Emergency Medicine residency program.…”
Section: Discussionmentioning
confidence: 99%
“…Medical therapy has been shown to be equally effective to drainage and resulted in fewer sick days in some patients, lower opioid usage, and decreased soreness [ 1 ]. However, I&D exhibits a success rate of 93-95%, and is a relatively inexpensive and simple procedure, making it the most common treatment approach [ 11 , 12 ]. Therefore, the primary objective of this study was to evaluate how a local hospital network’s EDs compared to generally accepted guidelines regarding the diagnosis and management of potential PTAs with respect to attempted drainage, appropriate antimicrobial therapy, and outpatient management.…”
Section: Introductionmentioning
confidence: 99%
“…Pre- and post-training surveys demonstrated significant improvements in comfort with the donning/doffing and tracheostomy protocols, underscoring the importance of simulation and rehearsal when planning such implementations. Previous authors have used similar models to assess otolaryngologist comfort pre/post simulation, and found that otolaryngologists are more likely to accurately predict their pre-intervention knowledge than are primary care providers [ 18 , 19 ]. In addition, decay in knowledge and comfort appears to occur more slowly in otolaryngology providers, when topics are within their field of practice.…”
Section: Discussionmentioning
confidence: 99%
“…Using materials costing only $2, an additional potential benefit of this study is to demonstrate that this simulator can be used to train healthcare providers in this important ultrasound skill. Simulators have the advantage of allowing providers to learn and practice skills prior to their application on patients, and other ultrasound simulators have been designed for this purpose [30]. Additional strengths of this study include 1) recorded images with quality assurance 2) different types of healthcare workers involved in being trained 3) extended follow-up period to measure skills retention, and 4) empowering health care providers to read and interpret images in real time thereby saving critical time and need for specialized human resources (radiologists).…”
Section: Discussionmentioning
confidence: 99%